Sea cucumber community in the coastal area of the Bahoi Village,West Likupang Sub-district, North Minahasa District - Andia Tri Fritama Lumbu; Lawrence J. L. Lumingas; Gaspar D. Manu (Jurnal Ilmiah PLATAX, 2020)
This research is conducted in the coastal waters of Bahoi Village, West Likupang Sub-district, North Minahasa District with the aims to know the types of sea-related environmental factors in the research site and know the community structure of the sea cucumber including the density, Index of diversity, dominance index, and distribution patterns. Data collection was done by using the line transect method, and sampling technique by using quadrat. The results of the study found 5 species of sea cucumber i.e. Holothuria atra,  Holothuria scabra,  Bohadschia marmorata, Actinopyga echinites, and  Bohadschia vitiensis. The individual density of all species is 0.12 ind/m2, and the diversity index (H ') 0.950. The value of the similarity index/compatibility obtained is e = 0.918. The result of the calculated dominance index of sea cucumber species is 1.0 and the pattern of spreading species of sea cucumber in the research site shows a random spread pattern because the value of dispersion index  (I) approaches 1 (one). Keywords: community; Sea cucumber; Bahoi; Dominance; Diversity.AbstrakPenelitian ini dilakukan di perairan pantai desa Bahoi, Kecamatan Likupang Barat, Kabupaten Minahasa Utara dengan tujuan untuk mengetahui jenis-jenis teripang yang ada di lokasi penelitian dan mengetahui struktur komunitas teripang yang meliputi kepadatan, indeks keanekaragaman, indeks dominasi, dan pola penyebaran. Pengambilan data dilakukan dengan metode line transek, dan teknik pengambilan sampel dengan mengunakan kuadrat. Hasil penelitian ditemukan 5 spesies teripang yaitu Holothuria atra, Holothuria scabra, Bohadschia marmorata, Actinopyga echinites dan Bohadschia vitiensis. Kepadatan individu dari seluruh spesies yaitu 0,12 ind/m2, indeks keanekaragaman (H’) 0,950. Nilai indeks kemerataan/keserasian diperoleh nilai indeks e = 0,918. nilai indeks dominasi spesies teripang diperoleh 1,0 dan pola penyebaran spesies teripang dilokasi penelitian menunjukkan pola sebaran acak (random) dikarenakan nilai indeks dispersi (I) mendekati 1 (satu).Kata Kunci : Komunitas; Teripang; Perairan Bahoi; Dominasi; Keanekaragaman